2015
DOI: 10.1016/j.bbadis.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 ameliorates kidney ischemia-reperfusion injury in mice through extracellular signal-regulated kinase 1/2-enhanced tubular epithelium proliferation

Abstract: Heme oxygenase (HO)-1 confers transient resistance against oxidative damage, including renal ischemia-reperfusion injury (IRI). We investigated the potential protective effect of HO-1 induction in a mouse model of renal IRI induced by bilateral clamping of the kidney arteries. The mice were randomly assigned to five groups to receive an intraperitoneal injection of PBS, hemin (an HO-1 inducer, 100μmol/kg), hemin+ZnPP (an HO-1 inhibitor, 5mg/kg), hemin+PD98059 (a MEK-ERK inhibitor, 10mg/kg) or a sham operation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…It has been shown that HO-1 induction ameliorates acute and chronic kidney injury such as ischemia-reperfusion (Chen et al 2015), cisplatin (Al-Kahtani et al 2014), and 5/6 nephrectomy (Desbuards et al 2009). On the other hand, the inhibition of this enzyme was found to aggravate renal damage (Ishikawa et al 2001;Takizawa et al 1998).…”
Section: R a F Tmentioning
confidence: 99%
“…It has been shown that HO-1 induction ameliorates acute and chronic kidney injury such as ischemia-reperfusion (Chen et al 2015), cisplatin (Al-Kahtani et al 2014), and 5/6 nephrectomy (Desbuards et al 2009). On the other hand, the inhibition of this enzyme was found to aggravate renal damage (Ishikawa et al 2001;Takizawa et al 1998).…”
Section: R a F Tmentioning
confidence: 99%
“…When IRI occurs, Keap1 undergoes conformational change and activates Nrf2, resulting in cellular protection against oxidative stress and enhancement of cell growth and survival [12, 13]. Hemeoxygenase-1 (HO-1) is one of the antioxidant response element (ARE)–dependent phase II detoxifying enzymes and antioxidants that are regulated by the redox-sensitive transcription factor Nrf2 [14-16]. Activation of Nrf2 induces HO-1 expression, suggesting that Nrf2 is essential for HO-1–mediated cytoprotection against IRI [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Total and phosphorylated ERK1/2 and p38 proteins were measured in NRK-52E cells exposed to 24 to 72 h of hypoxia. As shown in Figure 2 (A and B), hypoxia induced a large increase in phosphorylated ERK1/2 (P-ERK1/2) in the NRK-52E cells at all 3 time points (24,48, and 72 h) of hypoxic exposure (P < 0.001, n ¼ 4) without any significant change in total ERK 1/2 (T-ERK1/2) or ERK1/2 messenger RNA (Fig. 3).…”
Section: Effect Of Hypoxia On Erk1/2 and P38 Phosphorylationmentioning
confidence: 73%
“…44,45 Among them, the role of ERK1/2 has been considered a protective factor for cell survival, while p38 is considered a factor for cell injury. 20,[46][47][48][49] In cultured rat cortical neurons, hypoxia differentially regulated the phosphorylation of p38 and ERK1/2, 27 whereas in the rat hippocampal slices, the phosphorylation of both p38 and ERK2, but not ERK1, was upregulated in response to hypoxia. 50 It is also reported that chronic inflammatory and apoptotic cascades that are stimulated by p38 and JNK, but not ERK pathways, contribute to the pathogenesis of the chronic intermittent hypoxia-induced renal injury.…”
Section: Discussionmentioning
confidence: 97%